Kaleidoscope Byung-Chul Han - Bittencourt, Renato Nunes (Aoristo - International Journal of Phenomenology, Hermeneutics and Metaphysics, 2023)
he work of Byung-Chul Han rightfully gains prominence in the global philosophical scene. The most diverse topics of our challenging modernity are analysed by this provocative thinker, encompassing all philosophical spheres. Many consolidated views are deconstructed, and alternative proposals are highlighted for new understandings of today's world. Byung-Chul Han gives philosophical dignity to issues that directly involve our ways of life in an exhausted civilization. Discussing the fabric of the society of fatigue, the idea of positivity, the complexity of Burnout Syndrome, Infocracy, and other related themes, Byung-Chul Han articulates ontology, ethics, politics, economics, aesthetics, epistemology, and other discourses in a valuable exercise of transposing intellectual borders.